Excursions in world music - Nettl, Bruno 1930-; Rommen, Timothy; Wong, Isabel K. F.; Capwell, Charles; Turino, Thomas; Bohlmam, Philip V.; Dueck, Byron; Jankowsky, Richard; Pilzer, Joshua D.; Sykes, Jim (Routledge, 2017)
The new seventh edition introduces five brand new chapters, including chapters by three new contributors on the Middle east, South Asia, and Korea, as well as a new chapter on Latin America along with a new introduction written by Timothy Rommen. General updates have been made to other among ethnomusicologists who want students to explore the in-depth knowledge and scholarship that animates regional studies of world music.--Back cover